The impact of wheat production on the occurrence of mycotoxins DON (deoxynivalenol) and ZEA (zearalenone) on wheat grains (Triticum aestivum L.) - Lena TAJNŠEK; Marjan SIMČIČ; Anton TAJNŠEK (Acta Agriculturae Slovenica, 2014)
The current study has been conceived to draw attention to the factors that should be avoided in the production of cereal grains (such as high doses of nitrogen) by analysing differences in cereal grain contamination with mycotoxins DON (deoxynivalenol) and ZEA (zearalenone), depending on methods of wheat production. We studied the occurrence of DON and ZEA at very different production intensities in the ‘Reska’ and ‘Savinja’ wheat cultivars which were grown in a long-term field experiment (designed in 1992) at Jable near Ljubljana in the years 2006 and 2008. The cultivars ‘Reska’ and ‘Savinja’ have been considered in crop rotation of wheat-maize-oats in 5 methods of production with variants ranging organic up to intensely conventional. The results obtained have shown that adequately chosen agri-technical measures significantly reduced the risk of contamination of wheat flour by the mycotoxins DON and ZEA. Too abundant N (nitrogen) fertilization of either inorganic or organic origin is to be avoided. The extensive wheat growing reduces considerably the risk of DON and ZEA occurrence in comparison to the intensive one. Cultivar plays an important role in this process. The comparison of both cultivars has shown that the cultivar ‘Savinja’ was more resistant to the contamination with DON and ZEA than the cultivar ‘Reska’.